The nature and characteristics of the activities and development of retail trade enterprises - Toshpulatov Babur Rasul oglu (THE INNOVATION ECONOMY, 2026)
The article presents the opinions of foreign and domestic scientists about trade organizations, in particular retail trade, and provides a classification of types of trade enterprise development. The author’s proposals on approaches to managing the development of retail trade enterprises, taking into account their economic situation and the conditions of the consumer market of the Republic of Uzbekistan, are also presented.